\(log\left(x-5\right)< 2\)

b) 

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

a: \(log\left(x-5\right)< 2\)

=>\(\left\{{}\begin{matrix}x-5>0\\log\left(x-5\right)< log4\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}x-5>0\\x-5< 4\end{matrix}\right.\Leftrightarrow5< x< 9\)

b: \(log_2\left(2x-3\right)>4\)

=>\(log_2\left(2x-3\right)>log_216\)

=>\(\left\{{}\begin{matrix}2x-3>0\\2x-3>16\end{matrix}\right.\)

=>2x-3>16

=>2x>19

=>\(x>\dfrac{19}{2}\)

c: \(log_3\left(2x+5\right)< =3\)

=>\(log_3\left(2x+5\right)< =log_327\)

=>\(\left\{{}\begin{matrix}2x+5>0\\2x+5< =27\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}x>-\dfrac{5}{2}\\x< =11\end{matrix}\right.\)

=>\(-\dfrac{5}{2}< x< =11\)

d: \(log_4\left(4x-5\right)>=2\)

=>\(log_4\left(4x-5\right)>=log_416\)

=>4x-5>=16 và 4x-5>0

=>4x>=21 và 4x>5

=>4x>=21

=>\(x>=\dfrac{21}{4}\)

e: \(log_3\left(1-3x\right)>3\)

=>\(log_3\left(1-3x\right)>log_327\)

=>\(\left\{{}\begin{matrix}1-3x>0\\1-3x>27\end{matrix}\right.\)

=>1-3x>27

=>\(-3x>26\)

=>\(x< -\dfrac{26}{3}\)

22 tháng 9 2020

a. \(sin\left(4x+\pi\right)=sin35^o\)

\(\Leftrightarrow sin\left(4x+180^o\right)=sin35^o\)

\(\Leftrightarrow\left[{}\begin{matrix}4x+180^o=35^o+k.360^o,k\in Z\\4x+180^o=180^o-35^o+k.360^o,k\in Z\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}4x=-145^o+k.360^o,k\in Z\\4x=-35^o+k.360^o,k\in Z\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-\frac{145^o}{4}+k.90,k\in Z\\x=-\frac{35^o}{4}+k.90^o,k\in Z\end{matrix}\right.\)

Vậy.....

b.\(sin4x=\frac{1}{5}\)

\(\Leftrightarrow\left[{}\begin{matrix}4x=arcsin\left(\frac{1}{5}\right)+k2\pi,k\in Z\\4x=\pi-arcsin\left(\frac{1}{5}\right)+k2\pi,k\in Z\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\frac{arcsin\left(\frac{1}{5}\right)}{4}+\frac{k\pi}{2},k\in Z\\x=\frac{\pi}{4}-\frac{arcsin\left(\frac{1}{5}\right)}{4}+\frac{k\pi}{2},k\in Z\end{matrix}\right.\)

Vậy....

22 tháng 9 2020

c. \(sin\left(x+\frac{8\pi}{7}\right)=3\)

Ta có: \(-1\le sinx\le1\)

\(\Rightarrow-1\le sin\left(3x+\frac{8\pi}{7}\right)\le1\)

Do đó phương trình trên vô nghiệm

d. \(sinx=-7\)

Ta có: \(-1\le sinx\le1\)

Do đó phương trình trên vô nghiệm

e. \(sin\left(3x+\pi\right)=sin\left(2x-3\pi\right)\)

\(\Leftrightarrow\left[{}\begin{matrix}3x+\pi=2x-3\pi+k2\pi,k\in Z\\3x+\pi=\pi-2x+3\pi+k2\pi,k\in Z\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-4\pi+k2\pi,k\in Z\\5x=3\pi+k2\pi,k\in Z\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-4\pi+k2\pi,k\in Z\\x=\frac{3}{5}\pi+\frac{k2\pi}{5},k\in Z\end{matrix}\right.\)

Vậy......

f. \(sin\left(4x-\frac{\pi}{2}\right)=sin\left(\pi-2x\right)\)

\(\Leftrightarrow\left[{}\begin{matrix}4x-\frac{\pi}{2}=\pi-2x+k2\pi,k\in Z\\4x-\frac{\pi}{2}=\pi-\pi+2x+k2\pi,k\in Z\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}6x=\frac{3}{2}\pi+k2\pi,k\in Z\\2x=\frac{\pi}{2}+k2\pi,k\in Z\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\frac{\pi}{4}+\frac{k\pi}{3},k\in Z\\x=\frac{\pi}{4}+k\pi,k\in Z\end{matrix}\right.\)

Vậy......

NV
26 tháng 7 2020

e/

ĐKXĐ: ...

\(\Leftrightarrow\frac{1}{cos^2x}\left(9-13cosx\right)+4=0\)

\(\Leftrightarrow\frac{9}{cos^2x}-\frac{13}{cosx}+4=0\)

Đặt \(\frac{1}{cosx}=t\)

\(\Rightarrow9t^2-13t+4=0\)

\(\Rightarrow\left[{}\begin{matrix}t=1\\t=\frac{4}{9}\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}\frac{1}{cosx}=1\\\frac{1}{cosx}=\frac{4}{9}\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}cosx=1\\cosx=\frac{9}{4}>1\left(l\right)\end{matrix}\right.\)

\(\Rightarrow x=k2\pi\)

NV
26 tháng 7 2020

d/

\(\Leftrightarrow cos^22x+\frac{1}{2}+\frac{1}{2}cos\left(2x-\frac{\pi}{2}\right)-1=0\)

\(\Leftrightarrow1-sin^22x+\frac{1}{2}sin2x-\frac{1}{2}=0\)

\(\Leftrightarrow-2sin^22x+sin2x+1=0\)

\(\Rightarrow\left[{}\begin{matrix}sin2x=1\\sin2x=-\frac{1}{2}\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}2x=\frac{\pi}{2}+k2\pi\\2x=-\frac{\pi}{6}+k2\pi\\2x=\frac{7\pi}{6}+k2\pi\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=\frac{\pi}{4}+k\pi\\x=-\frac{\pi}{12}+k\pi\\x=\frac{7\pi}{12}+k\pi\end{matrix}\right.\)

NV
16 tháng 9 2020

c.

\(\Leftrightarrow sin\left(3x+\frac{2\pi}{3}\right)=-sin\left(x-\frac{2\pi}{5}-\pi\right)\)

\(\Leftrightarrow sin\left(3x+\frac{2\pi}{3}\right)=sin\left(x-\frac{2\pi}{5}\right)\)

\(\Leftrightarrow\left[{}\begin{matrix}3x+\frac{2\pi}{3}=x-\frac{2\pi}{5}+k2\pi\\3x+\frac{2\pi}{3}=\frac{7\pi}{5}-x+k2\pi\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-\frac{8\pi}{15}+k\pi\\x=\frac{11\pi}{60}+\frac{k\pi}{2}\end{matrix}\right.\)

d.

\(\Leftrightarrow cos\left(4x+\frac{\pi}{3}\right)=sin\left(\frac{\pi}{4}-x\right)\)

\(\Leftrightarrow cos\left(4x+\frac{\pi}{3}\right)=cos\left(\frac{\pi}{4}+x\right)\)

\(\Leftrightarrow\left[{}\begin{matrix}4x+\frac{\pi}{3}=\frac{\pi}{4}+x+k2\pi\\4x+\frac{\pi}{3}=-\frac{\pi}{4}-x+k2\pi\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-\frac{\pi}{36}+\frac{k2\pi}{3}\\x=-\frac{7\pi}{60}+\frac{k2\pi}{5}\end{matrix}\right.\)

NV
16 tháng 9 2020

a.

\(sin\left(2x+1\right)=-cos\left(3x-1\right)\)

\(\Leftrightarrow sin\left(2x+1\right)=sin\left(3x-1-\frac{\pi}{2}\right)\)

\(\Leftrightarrow\left[{}\begin{matrix}3x-1-\frac{\pi}{2}=2x+1+k2\pi\\3x-1-\frac{\pi}{2}=\pi-2x-1+k2\pi\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\frac{\pi}{2}+2+k2\pi\\x=\frac{3\pi}{10}+\frac{k2\pi}{5}\end{matrix}\right.\)

b.

\(sin\left(2x-\frac{\pi}{6}\right)=sin\left(\frac{\pi}{4}-x\right)\)

\(\Leftrightarrow\left[{}\begin{matrix}2x-\frac{\pi}{6}=\frac{\pi}{4}-x+k2\pi\\2x-\frac{\pi}{6}=\frac{3\pi}{4}+x+k2\pi\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\frac{5\pi}{36}+\frac{k2\pi}{3}\\x=\frac{11\pi}{12}+k2\pi\end{matrix}\right.\)

Tham khảo:

undefined

4 tháng 4 2017

Lời giải:

a) Ta có f'(x) = 3x2 + 1, g(x) = 6x + 1. Do đó

f'(x) > g'(x) <=> 3x2 + 1 > 6x + 1 <=> 3x2 - 6x >0

<=> 3x(x - 2) > 0 <=> x > 2 hoặc x > 0 <=> x ∈ (-∞;0) ∪ (2;+∞).

b) Ta có f'(x) = 6x2 - 2x, g'(x) = 3x2 + x. Do đó

f'(x) > g'(x) <=> 6x2 - 2x > 3x2 + x <=> 3x2 - 3x > 0

<=> 3x(x - 1) > 0 <=> x > 1 hoặc x < 0 <=> x ∈ (-∞;0) ∪ (1;+∞).



8 tháng 9 2016

b)đề là \(tan\left(x-15^0\right)=\frac{\sqrt{3}}{3}\)

Vì \(\frac{\sqrt{3}}{3}=tan30^0\) nên

\(\Leftrightarrow tan\left(x-15^0\right)=tan30^0\)

\(\Leftrightarrow x-15^0=30^0+k180^0\)

\(\Leftrightarrow x=45^0+k180^0\left(k\in Z\right)\)

8 tháng 9 2016

Đk:\(sin3x\ne0\) và \(cos\frac{2\pi}{5}\ne0\)

\(\Leftrightarrow\frac{cos3x}{sin3x}-\frac{sin\frac{2\pi}{5}}{cos\frac{2\pi}{5}}=0\)

\(\Leftrightarrow cos3x\cdot cos\frac{2\pi}{5}-sin\frac{2\pi}{5}\cdot sin3x=0\)

\(\Leftrightarrow cos\left(3x+\frac{2\pi}{5}\right)=0\)

\(\Leftrightarrow3x+\frac{2\pi}{5}=\frac{\pi}{2}+k\pi\)

\(\Leftrightarrow x=\frac{\pi}{30}+\frac{k\pi}{3}\)